Earthquake engineering proceedings of 14th Symposium on Earthquake Engineering, held at Indian Institute of Technology, Roorkee, December 17-19, 2010 - Kumar, Ashwani; Sharma, M.L (Elite Publishing House Pvt Ltd, 2010)
Contributed articles presented at the symposium; organized by the Dept. of Earthquake Engineering, Indian Institute of Technology, Roorkee